Preventive Effect of Chimonanthus praecox Flower Extract on High-fat Diet-induced Obesity in Mice - Min ZHOU; Hao YANG; Tingyao ZHANG; Chunpeng CHEN; Shuangjiang LEI; Shirong JIAO (Shipin gongye ke-ji, 2024)
Objective: To study the preventive effect of ethanolic extract from Chimonanthus praecox flower on obesity induced by high-fat diet in mice. Methods: A total of 50 C57BL/6 mice were divided into five groups of blank control, model control, low-, medium- and high-dose Chimonanthus praecox flower extract (CPFE) treatment. The mice in the blank control group were provided with a basal diet whereas those in the other groups were given a high-fat diet. The mice in the low-, medium- and high-dose groups were orally administered with CPFE at doses of 0.2, 0.4 and 0.8 g/(kg mb·d), containing 24.81, 49.62 and 99.25 mg/(kg mb·d) of Chimonanthus praecox flower polyphenols, respectively. The blank control, model control groups were administered with 0.9% NaCl. The administration lasted for 4 weeks. Then, body weight, serum biochemical indicators, organ antioxidant capacity were measured and pathological sections of liver tissue were examined. Results: The body weight, liver coefficient, serum levels of TC, LDL-C, organ levels of MDA in the model control group were significantly higher than those in the blank control group (P<0.05). The levels of organ GSH-Px, CAT, SOD, GSH in the model control group were significantly lower than those in the blank control group (P<0.05). Pathological examination showed that compared with the blank control group, the structure of liver lobules was irregular, the cell morphology was destroyed, vacuolar degeneration occurs, and the hepatic cord was not clear, and the hepatic sinuses were squeezed and deformed, indicating successful obesity induction in mice. In addition, compared with the model control group, the CPFE especially at the high dose lowered serum TC, LDL-C, TG, organ MDA in obese mice (P<0.05) and increased serum HDL-C levels, organ GSH-Px, CAT, SOD, GSH levels, and the effect was dose-effective with the concentration of CPFE. Pathological status of the organ were improved compared to the model control group, as evidenced by a more intact liver histomorphology and structure. The extract also reduced the body weight and liver index of obese mice and the effect was more pronounced in the high dose group. Conclusion: The CPFE have the effects of lowering serum cholesterol, enhancing antioxidant capacity and protecting the functional morphology of liver tissue cells in mice.